Essential Oil Formulation for Ultrasonic Diffuser Products Based on Aroma Characteristics and Aroma Durability - Daimon Syukri; Aisman Aisman; Rini Rini; Aisyah Putri; Luwina Makni Kusuma; Rafifa Putria Dewita; Napassawan Liamnimitr (Open Global Scientific Journal, 2026)
Background: Aromatherapy is a complementary treatment method that provides relaxation, improves mood, and enhances psychological well-being. However, formulating aromatherapy materials presents challenges due to the volatility of the base ingredients, which are essential oils. Therefore, optimal essential oil formulations are necessary.Aims: This study aims to obtain an optimal essential oil formulation for making diffuser oils based on ultrasonic technology. The essential oils used consist of kaffir lime (Citrus hystrix), ylang-ylang (Cananga odorata), bergamot (Citrus bergamia), rosemary (Rosmarinus officinalis L.), eucalyptus (Melaleuca cajuputi), peppermint (Mentha piperita), and patchouli (Pogostemon cablin Benth.) oils.Methods: Formulation development was carried out in two stages. In the initial stage, five formulations were developed based on a combination of citrus, floral, herbal, and fixative aroma characteristics. This stage was carried out to obtain a representative variety of aroma profiles before further selection. Based on the initial evaluation, the three best formulations (F1, F3, and F5) were selected for further testing. Organoleptic testing was conducted on 30 untrained panelists by assessing three parameters: aroma preference level, aroma strength, and aroma quality using the direct olfactory method. The aroma durability test was conducted for 12 hours with aroma intensity observations every two hours.Results: The results showed that formulation F3 achieved the highest preference scores across all organoleptic parameters and demonstrated the best aroma durability throughout the testing period. The combination of citrus and floral essential oils with patchouli oil as a fixative produced a more balanced aroma, was accepted by panelists, and lasted longer than the other formulations.Conclusion: The combination of citrus and floral essential oils with patchouli oil as a fixative produced good aromatherapy. This research contributes to the development of natural essential oil-based diffuser oil formulations and provides scientific information on the effect of essential oil combinations on consumer acceptance and aroma durability in ultrasonic diffusers.